Electromyographic analysis of impingement syndrome: Comparison in volleyball athletes - Oliveira, Leonor (2011)
The purpose of this study was to analyze the muscle activity of the trunk and shoulder complex during the volleyball serve and the possible correlation with the mechanisms of injury of impingement syndrome (IS). The athletes (female, n=15) were divided in three groups: 1) with pain, 2) without pain but with history of shoulder pain, and 3) without pain. Surface electromyographic data were collected from shoulder and trunk muscles and synchronized with video image recorded at high-speed. The data analysis revealed an increased activity in both Upper Trapezius and Infraespinatus and a decreased activity in Rectus Abdominus and External Oblique in the group with IS.